Analisis Modal Kerja dan Profitabilitas pada PT. Jolulutara Inti Pratama Balikpapan - Julius Aido P. Simanjuntak; Ardi Paminto; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
In this thesis, the basic idea is about Working Capital and Profitability. The purpose of this study was to determine the level of working capital at PT. Jolulutara Inti Pratama to generate its profit from the year 2012 to 2014. To analyze the data, the authors used an analysis tool as seen from the working capital and the profitability of current assets by proxy, net profit margin, basic earning power, return on investment and return on equity. From these results, it can be concluded that the Working Capital and Profitability in PT Inti Pratama Jolulutara years 2012-2014 tends to fluctuate. Use of Working Capital inefficient resulting in instability of the profitability of the company in achieving corporate goals.Keywords: Working capital, Profitability, net profit margin, basic earning power, return on                                         investment, return on equity.